Strategy of Revascularization for Critical Limb Ischemia Due to Infragenicular Lesions—Which Should be Selected Firstly, Bypass Surgery or Endovascular Therapy? - Iwasa, Kazuomi; Ohmine, Takahiro; Yamaoka, Terutoshi (Japanese Journal of Vascular Surgery, 2014)
Background and Objectives: In patients with peripheral arterial diseases (PADs) due to infra-popliteal (below-the-knee; BTK) lesions, we often encounter situations requiring the immediate selection of either of two revascularization methods, namely bypass surgery or endovascular therapy (EVT). However, the question of whether endovascular or surgical revascularization should be performed initially for critical limb ischemia (CLI) patients with BTK lesions has not been clarified. To assess the efficacy and durability of EVT or bypass as a first approach, we evaluated the short- and mid-term outcomes of the first revascularizations achieved using EVT (EVT First Group; EVT-first) compared with bypass (Bypass First Group; Bypass-first). To verify the validity of each initial revascularization, we explored factors influencing overall survival (OS) rates using multivariate analyses. Methods: A total of 169 consecutive BTK revascularization procedures (150 patients) for CLI conducted at our facility between November 2006 and July 2012 were analyzed. Patients undergoing revascularization were divided into two groups (EVT-first or Bypass-first), with 102 patients undergoing endovascular therapy first (EVT-first) and 51 undergoing bypass surgery first (Bypass-first). No statistically significant differences were noted between the two groups with respect to preoperative background including age, gender, and cardiovascular risk factors (hypertension, diabetes, hyperlipidemia, coronary arterial disease (CAD), chronic heart failure (CHF), cerebrovascular disease, and hemodialysis). Technical success was defined as a single straight-line flow to the ankle after completion angiography of the first revascularization method. Hemodynamic success was defined as a postoperative skin perfusion pressure of the foot exceeding 40 mmHg. Results: The average age of patients was 76.0 years (range, 46–98 years; 65 men and 37 women) and 72.3 years (range, 43–93 years; 35 men and 13 women) in the EVT-first and Bypass-first groups, respectively. Patient follow-up ranged from 1 to 50 months (mean, 15 months). Respective technical and hemodynamic success rates were 96.2% and 66.7% for EVT-first and 100% and 94% for Bypass-first, respectively. Treatment was required an average of 1.5 times for EVT-first and 1.2 times for Bypass-first. Respective rates for other factors examined in the EVT-first and the Bypass-first groups were: major amputation rates 30 days post-procedure, 5.9%, and 3.9%; mortality rates 30 days post-procedure, 3.9%, and 0%; one-year AFS rates, 71.7%, and 79.5%; OS rates, 73.5% and 83.9%; and limb salvage rates, 88.8%, and 91.0%. Multivariate-analysis of all subjects in the two groups revealed that the OS rates was affected by four risk factors as follows: 1) age greater than 80 years, 2) CAD, 3) CHF, and 4) a non-ambulatory limb. Conclusion: For patients with CLI due to BTK lesions and whose saphenous veins are in poor condition or are in poor general condition having two or more of the four severe risk factors, the EVT-First procedure is effective and provides durable results. Overall survival in patients with CLI due to BTK lesions is worse when patients have more than two severe risk factors, which is non-ambulatory limb, aged less than 81 years, with CAD or with CHF.